A process for treatment of palm oil mill effluent and for conversion of the palm oil mill effluent into biodegradable plastics - Hassan, Mohd Ali (2006)

(untitled)
A process is described for converting organic materials from liquid oil mill affluent into a bioplastic suitable for use as a biodegradable plastic. In a preferred embodiment the process involves anaerobic treatment of palm oil moll effluent (POME) with digested sludge at pH of about to produce organic acid, particularly acetic and propionic, the solid of POME is removed by sodium hydroxide precipitation at pH of about 12. The clarified fraction of POME is then inoculated with photosynthesis bacterium of Rhodobacter species which accumulates the bioplastic by the cells utilising the organic acids produced and certrifugation by drying and solvent extraction for the recovery of the bioplastic.